Genome sequence of classical Swine Fever Virus NIVEDI-165, Subtype 1.1, a field virus strain isolated from the southern part of India - Patil, S.S.; Suresh, K.P.; Amachawadi, R.G.; Meekins, D.A.; Richt, J.A.; Mondal, M.; Hiremath, J.; Hemadri, D.; Rahman, Habibur; Roy, P. (American Society for Microbiology, 2019)
The whole-genome sequence of an Indian field isolate of classical swine fever virus, NIVEDI-165, was found to be subtype 1.1, and it showed 89 to 99% amino acid identity and 84 to 99% nucleotide identity with four and five Indian classical swine fever virus (CSFV) isolates, respectively. To the best of our knowledge, this is the first report on a full-genome sequence of CSFV from South India.